2013
DOI: 10.1101/gad.203760.112
|View full text |Cite
|
Sign up to set email alerts
|

SRC-3 coactivator regulates cell resistance to cytotoxic stress via TRAF4-mediated p53 destabilization

Abstract: Steroid receptor coactivator 3 (SRC-3) is an oncogenic nuclear receptor coactivator that plays a significant role in drug resistance. Using a lentiviral cDNA library rescue screening approach, we identified a SRC-3 downstream gene-TRAF4 (tumor necrosis factor [TNF] receptor associated-factor 4)-that functions in cell resistance to cytotoxic stress. TRAF4 expression is positively correlated with SRC-3 expression in human breast cancers. Similar to that observed for SRC-3 overexpression, breast cancer cells over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Forced overexpression of SRC-3 in mammary epithelial cells has been shown to be sufficient to promote mammary tumor formation, directly indicating it in breast cancer initiation (Lanz et al, 2010). Consistently, mice with SRC-3 deletion had suppressed oncogene-and carcinogen-induced breast cancer initiation, progression, and metastasis (Kuang et al, 2004;Yi et al, 2013). Moreover, overexpression of SRC-3 has been frequently observed in a variety of other cancer types including lung, ovarian, liver, colorectal, pancreatic, and prostate cancers (Long et al, 2012;Palmieri et al, 2013;Geng et al, 2013).…”
Section: Introductionmentioning
confidence: 61%
“…Forced overexpression of SRC-3 in mammary epithelial cells has been shown to be sufficient to promote mammary tumor formation, directly indicating it in breast cancer initiation (Lanz et al, 2010). Consistently, mice with SRC-3 deletion had suppressed oncogene-and carcinogen-induced breast cancer initiation, progression, and metastasis (Kuang et al, 2004;Yi et al, 2013). Moreover, overexpression of SRC-3 has been frequently observed in a variety of other cancer types including lung, ovarian, liver, colorectal, pancreatic, and prostate cancers (Long et al, 2012;Palmieri et al, 2013;Geng et al, 2013).…”
Section: Introductionmentioning
confidence: 61%
“…Indeed, TRAF4 was shown to bind and inactivate the deubiquitinase HAUSP (herpesvirus-associated ubiquitin-specific protease). 20 HAUSP antagonizes the action of MDM2 on P53. While the E3-ligase MDM2 ubiquitinates p53 to induce its proteasomal degradation, HAUSP deubiquitinates P53 and stabilizes the protein.…”
Section: Traf4 Weakens Tight Junctions and Favors Cell Migration 2 Cmentioning
confidence: 94%
“…Once TJ are destroyed, TRAF4 is more abundant in the cytoplasm and/or in the nucleus 8,9,16,20 ; its role in these compartments remained unclear. A recent study addressed the role of TRAF4 in signaling events occurring in the cytoplasm and in the nucleus.…”
Section: Traf4 Weakens Tight Junctions and Favors Cell Migration 2 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous research also demonstrated GA restrains the growth of xenografted GCB-and ABC-DLBCL cells in nude mice (Shi et al, 2015). In consideration of the therapy-resistant role of overexpressed SRC-3, inhibition of SRC-3 was also required in cancer chemotherapy especially for those chemoresistant cancers (Colo et al, 2007;Tien and Xu, 2012;Yi et al, 2013). GA could be used in combination with conventional chemotherapy to relieve the chemoresistance of cancer.…”
Section: Discussionmentioning
confidence: 99%